Analisis Perubahan Manajemen Operasional Pt. Sanipak Indonesia - Teresia Armeta H; Tirani Apriyana; Adzra Afifah Pratiwi; Kesha Katrillah; Nova Natasha; Benny Benny (Jurnal Mirai Management, 2023)
Companies and every organization that exists certainly depends on how operations take place. The company's performance is also determined based on the effective and efficient implementation of operational management. The intense competition that continues to be experienced by industry players, including the manufacturing industry, requires them to maintain the company's existence by managing operational management as best as possible. PT. Sanipak Indonesia as a manufacturer of plastic waste production. This study uses a qualitative descriptive method using secondary data from previous studies and observational data on the operations of PT. Sanipak Indonesia. This method is related to data collection methods, because in the library method data is obtained through journals, books, and digital and physical recording. Data analysis was carried out systematically, starting with data collection, data management, and drawing conclusions. Based on the results of the study concluded that PT. Sanipak Indonesia continues to experience problems before, during and after the pandemic. Before the pandemic the main obstacle was caused by machines but during the pandemic it spread to other operations such as limiting working hours and stagnant supplies of raw materials. The post-pandemic strategy includes updating production equipment, workforce recruitment and more supervision of the supply chain to ensure that raw materials are not constrained Kata Kunci: Operational Management, Manufacturing, Covid -19.